2017
DOI: 10.21278/brod68108
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Wake Evolution of Contra-Rotating Propeller in Propeller Open Water and Self-Propulsion Conditions

Abstract: SummaryIn this study, the wake characteristics of a contra-rotating propeller (CRP) were investigated using a numerical simulation. The numerical simulation was carried out with a Reynolds averaged Navier−Stokes equations solver. The numerical simulations were performed on CRPs in both propeller open water and self-propulsion conditions to investigate their wake evolution characteristics. To study the effect of the rudder on the wake in the selfpropulsion condition, the numerical simulations with and without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…They implemented CFD (computational fluid dynamics) based on RANS (Reynolds averaged Navier Stokes equation) methods to generate simulated results and compared them to experimental data. Palik [29] investigated the performance of a partially submerged propeller and also used RANS with a Bollard condition, i.e., the inflow velocity was zero. They conducted their research on the partially submerged horizontal vertically oriented propellers and reported good consistency between the models and the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…They implemented CFD (computational fluid dynamics) based on RANS (Reynolds averaged Navier Stokes equation) methods to generate simulated results and compared them to experimental data. Palik [29] investigated the performance of a partially submerged propeller and also used RANS with a Bollard condition, i.e., the inflow velocity was zero. They conducted their research on the partially submerged horizontal vertically oriented propellers and reported good consistency between the models and the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that thrust and torque of partially submerged propeller decrease significantly with an increase in rate of revolution. In [16], the author has investigated wake characteristics of Contra Rotating Propeller (CRP) in OWT and self-propulsion conditions. In addition, Paik studied the effect of rudder on wake characteristics in self-propulsion test and concluded that the presence of the rudder has no significant influence on wake whereas a significant influence on thrust and torque was noticed.…”
mentioning
confidence: 99%